THE COMPUTATION EXPRESSIONS OF SPHEROIDAL EIGENVALUES - Wang, Wan-xian (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The higher order terms of eigenvalues in spheroidal differential equations are developed by using power-series expansion and asymptotic ones for both prolate and oblate wave functions. These important multipole expansions greatly facilitate and improve the computations of the electromagnetic scattering by different kinds of spheroids with various size parameters, refractive indices, and aspect ratios. [Vol. 2, No. 2, pp. 112-121 (1987)]